Sorptive Removal of Odorous Carbonyl Gases by Water - Ehsanul Kabir; Ki-Hyun Kim (The Scientific World Journal)
In this study, the removal capacity of deionized water was investigated against five gaseous carbonyl compounds (i.e., acetaldehyde, propionaldehyde, butyraldehyde, valeraldehyde, and isovaleraldehyde) by means of the gas stripping method. To determine the trapping behavior of these odorants by water, gaseous working standards prepared at three different concentration levels (i.e., for acetaldehyde around 300, 500, and 1,000 ppb) were forced through pure water contained in an impinger at room temperature. The removal efficiency of the target compounds was inspected in terms of two major variables: (1) concentration levels of gaseous standard and (2) impinger water volume (20, 50, 100, and 150 mL). Although the extent of removal was affected fairly sensitively by changes in water volume, this was not the case for standard concentration level changes. Considering the efficiency of sorption media, gas stripping with aqueous solution can be employed as an effective tool for the removal of carbonyl odorants.